2016
DOI: 10.1007/s00542-016-3193-8
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrocatalytic microreactor for seawater decontamination with negligible chlorine generation

Abstract: Decontamination of seawater is of particular importance for the waste seawater treatment before its drainage. However, some mature methods to clean waste fresh water cannot be employed to treat waste seawater due to its high slat concentration.Besides, excessive chlorine generation during the seawater decontamination process is toxic for sea creatures. In this work, a microfluidic reactor is designed and fabricated to enable the photoelectrocatalytic effect for highly-efficient seawater decontamination with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Microfluidic devices have intrinsic merits such as large surface area, high mass transfer, and easy integration [8][9][10][11] and thus have been widely developed for micro total analysis in rapid diagnosis 12 and water treatment. 13 Because of light, fluid, and its interaction involved, online monitoring of water quality using absorption spectrometry is a natural optofluidic system.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic devices have intrinsic merits such as large surface area, high mass transfer, and easy integration [8][9][10][11] and thus have been widely developed for micro total analysis in rapid diagnosis 12 and water treatment. 13 Because of light, fluid, and its interaction involved, online monitoring of water quality using absorption spectrometry is a natural optofluidic system.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus is one of the indispensable nutrients for all kinds of natural water. However, excessive phosphorus in water will cause eutrophication and seriously deteriorate the ecological environment [1][2][3]. Therefore, monitoring of total phosphate in surface water, sewage and industrial wastewater has become a focus all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…Optofluidics, which integrate synergistically photonics and microfluidics, shows the advantages of small size, high integration, and low power/reagent consumption . Optofluidics have inspired numerous on-chip devices with enhanced performance, , such as waveguides, , switches, transformation optics, , and biochemical sensors. Previous studies demonstrated these advantages by directly inserting the modules into a microfluidic chip for colorimetric analysis.…”
mentioning
confidence: 99%